Effect of thallium exposure and its interaction with smoking on lung function decline: A prospective cohort study. (June 2019) - Dai, Juanxiu; Wu, Xiulong; Bai, Yansen; Feng, Wei; Wang, Suhan; Chen, Zhuowang; Fu, Wenshan; Li, Guyanan; Chen, Weilin; Wang, Gege; Feng, Yue; Liu, Yuhang; et al.
Abstract: Background: Thallium (Tl) is a cumulative high toxicant in the environment, but few longitudinal studies have investigated the respiratory impairment of Tl exposure. Objectives: This study aimed to evaluate the effect of Tl and its interaction with smoking on lung function decline, and explore the potential mechanisms. Methods: The baseline and follow-up lung functions were measured from a prospective cohort study of 1243 workers, who were followed from 2010 to 2014. Their baseline urinary levels of Tl were determined. We also measured the plasma C-reactive protein (CRP) and urinary 8-iso-prostaglandin-F2α (8-iso-PGF2α) in a randomly selected subcohort of 474 subjects. Results: The results showed that a 2-fold increase in urinary Tl was associated with 29.81 mL (95%CI: 3.83–55.80) increased decline in forced expiratory volume in 1 s (FEV1 ). The effect was more pronounced among heavy-smokers (≥15 pack-years) [β(95%CI) = 56.42 mL (9.66–103.19)]. In particular, compared to never-smokers with low Tl, heavy-smokers with high Tl had a separate 158.44 mL (95%CI: 54.88–262.00) and 4.58% (95%CI: 1.40–7.76) increased declines in FEV1 and percentage of predicted (ppFEV1 ), respectively. There was a significant interaction between Tl and smoking intensity on ppFEV1 decline ( P int = 0.034). More importantly, the increasing level of urinary Tl was correlated with elevated CRP and 8-iso-PGF2α. Conclusion: Our prospective cohort study identified that exposure to high Tl had a deleterious effect on lung function, and this effect may be enhanced by tobacco smoking. Increased inflammation may partly contribute to the joint effects of Tl and smoking on impaired lung function, but the biological mechanisms need further explorations. Highlights: Urinary thallium was associated with increased 4-year's lung function decline. The impairment effect of Tl on lung function was enhanced by heavy smoking. There was significant interaction between Tl and smoking on decline in ppFEV1 . The urinary Tl was correlated with elevated levels of CRP and 8-iso-PGF2α.